2012
DOI: 10.1080/15226514.2011.607871
|View full text |Cite
|
Sign up to set email alerts
|

Using Pilot Test Data to Refine an Alternative Cover Design in Northern California

Abstract: Two instrumented test sections were constructed in summer 1999 at the Kiefer Landfill near Sacramento, California to test the hydraulic performance of two proposed alternative final covers. Both test sections simulated monolithic evapotranspiration (ET) designs that differed primarily in thickness. Both were seeded with a mix of two perennial and one annual grass species. Oleander seedlings were also planted in the thicker test section. Detailed hydrologic performance monitoring of the covers was conducted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Choosing species with higher growth rates like A. acuminata (Figure 3) may lead to better immediate vegetation coverage and water extraction thus increasing initial ET performance. However, it is important to consider that species with high initial biomass production and water use may outcompete species with slower biomass production and water use (Zea-Cabrera et al 2006), eventually resulting in decreased ET cover performance (Smesrud et al 2011). Additionally, the co-existence of species with varying growth and water use strategies may be necessary to attain balanced transpiration on ET covers (Gwenzi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Choosing species with higher growth rates like A. acuminata (Figure 3) may lead to better immediate vegetation coverage and water extraction thus increasing initial ET performance. However, it is important to consider that species with high initial biomass production and water use may outcompete species with slower biomass production and water use (Zea-Cabrera et al 2006), eventually resulting in decreased ET cover performance (Smesrud et al 2011). Additionally, the co-existence of species with varying growth and water use strategies may be necessary to attain balanced transpiration on ET covers (Gwenzi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate depletion in the spring and summer reduced the available water storage capacity the following winter, and insufficient capacity existed to store the winter infiltration. Consequently, the storage capacity was exceeded and significant percolation occurred in the winter of and the winter of 2003-2004. Smesrud et al (2012 decommissioned the test sections in Sacramento and determined that the original plant community comprised of perennial grasses transitioned to shallow-rooted annual grasses common in the surrounding landscape.…”
Section: Plant Transpirationmentioning
confidence: 99%
“…Consequently, the storage capacity was reduced, and the cover transmitted more percolation than intended. Water balance modeling conducted by Smesrud et al (2012) demonstrated that sufficient soil water storage capacity would have been available each year and percolation would have been minimal if the original perennial grasses had been maintained. The lesson from this site was to select vegetation that exists in the surrounding landscape if possible and to understand the transpiration capacity of the local vegetation (e.g., wilting point, root depth and distribution, growing season).…”
Section: Plant Transpirationmentioning
confidence: 99%
“…Therefore, given the historic climate of western New South Wales, it is not surprising that both intensive and extensive water users can prosper, and it is reasonable to expect that stable ecosystems can be established on engineered covers (Gwenzi et al, 2013). However, the initial re-establishment of these ecosystems might be challenging because intensive water users with elevated initial biomass production may outcompete extensive water users if both species show similar drought adaptations (Zea-Cabrera et al, 2006;Smesrud et al, 2012). Nevertheless, the coexistence of species with contrasting water use patterns is favoured by the irregular spatial distribution of soil moisture (Zea-Cabrera et al, 2006), which is likely to occur on reconstructed ecosystems because of the high likelihood of spatial heterogeneity of soil physical properties (Krümmelbein et al, 2010;Schneider et al, 2010;Gwenzi et al, 2011;Mazur et al, 2011).…”
Section: Implications For Et Cover Designmentioning
confidence: 99%
“…The plant contribution to ET from cover systems may vary from 44% to 93% in temperate Eastern Australia (Yunusa et al, 2010) to about 22% in Mediterranean Western Australia (Gwenzi, 2010). Furthermore, plant community maturity and composition are likely to substantially affect the water usage of vegetation (Barnswell and Dwyer, 2011;Smesrud et al, 2012). By contrast, empirical information about the effect of vegetation composition on ET losses from waste cover systems in semi-arid climates is limited.…”
Section: Introductionmentioning
confidence: 99%